Effect of naphthalene acetic acid on the adventitious rooting in shoot cuttings of Andrographis paniculata (Burm.f.) wall. ex Nees: an important therapeutical herb - Hossain, Md. Sanower; Phang, Ing Chia; Urbi, Zannat (Hindawi, 2017)
Andrographis paniculata is one of the most important therapeutical herbs, widely used in traditional medical systems for the treatment of diverse diseases for thousands of years. This study was carried out to assess the effect of 1-naphthaleneacetic acid (NAA) on adventitious rooting in A. paniculata shoot cuttings. The cuttings were treated with six concentrations of NAA (0.5, 1.0, 1.5, 2.0, 2.5, and 3.0 mM) by applying soaking method and cuttings without hormone (soaking in distilled water) were considered as control. The cuttings were then inoculated into peat moss in the planting tray and incubated under complete shade for root induction. Water was sprayed on peat moss once daily to moisten it. The results showed that different concentrations of NAA significantly () affected the rooting characteristics of A. paniculata and 2.5 mM of NAA was found to be more effective to induce rooting in young apical shoot (YAS) cuttings compared to other concentrations and old apical shoot (OAS). This study also postulates that adventitious rooting response depends on the juvenility of plant material and concentration of growth regulator. This report describes a technique for adventitious rooting in A. paniculata, which could be feasible to use for commercial scale propagation of this plant.